Durability Assessment of a Plasma-Polymerized Coating with Anti-Biofilm Activity against L. monocytogenes Subjected to Repeated Sanitization - Ignacio Muro-Fraguas (MDPI AG, 2021)
Biofilm formation on food-contact surfaces is a matter of major concern causing food safety and spoilage issues to this sector. The aim of this study was to assess the durability of the anti-biofilm capacity of a plasma-polymerized coating composed of a base coating of (3-aminopropyl)triethoxysilane (APTES) and a functional coating of acrylic acid (AcAc). Coated and uncoated AISI 316 stainless steel (SS) plates were subjected to five sanitization cycles with sodium hypochlorite (0.05%) and peracetic acid (0.5%). The effectiveness of the coating for the inhibition of multi-strain Listeria monocytogenes biofilm formation was confirmed using a three-strain cocktail, which was grown on the SS plates at 12 °C for 6 days. Compared to the uncoated SS, relative biofilm productions of 14.6% on the non-sanitized coating, 27.9% on the coating after sanitization with sodium hypochlorite, and 82.3% on the coating after sanitization with peracetic acid were obtained. Morphological and physicochemical characterization of the coatings suggested that the greater anti-biofilm effectiveness after sanitization with sodium hypochlorite was due to the high pH of this solution, which caused a deprotonation of the carboxylic acid groups of the functional coating. This fact conferred it a strong hydrophilicity and negatively charged its surface, which was favorable for preventing bacterial attachment and biofilm formation.